PENGARUH ALIH FUNGSI LAHAN SAWAH TERHADAP PRODUKSI PADI DI KABUPATEN GOWA PROVINSI SULAWESI-SELATAN - Aminuddin, - (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
There are uncertain pattern in the development of rice field function alteration tonon-rice field, where the alteration absolutely depends on various factors, such asthe development of office building (both public and privat), housing, roadway, etc.,in any sub-district at Kabupaten Gowa. The wide of field significantly affects on thetotal of rice production, but the in the level of 5%, the influence of function alterationof rice field to non-rice field statistically was not significant.Keywords: rice field function alteration and rice production